Centella asiatica prevents D-galactose-Induced cognitive deficits, oxidative stress and neurodegeneration in the adult rat brain - Firdaus Z.; Singh N.; Prajapati S.K.; Krishnamurthy S.; Singh T.D. (My University, 2025)
Chronic D-galactose (D-gal) administration causes cognitive impairment and is used widely in animal models for anti-aging studies. Centella asiatica (CA), a traditional herbal medicine, has been used as a brain tonic to enhance memory. This study evaluates the neuroprotective role of an ethanolic extract of Centella asiatica (CAE) against D-gal-induced aging in rats. Healthy male rats were divided into three groups: Control, D-gal, and D-gal + CAE. The Control group received normal saline (i.p.), whereas the D-gal group received D-gal (120 mg/kg b.w., i.p.), and the D-gal + CAE group received D-gal (120 mg/kg b.w., i.p.) and CAE (300 mg/kg b.w., orally) daily for 42 days. Behavioral and brain biochemical and histopathological changes were assessed after treatment. The results of the behavioral study depicted that D-gal significantly reduces the spontaneous alternation and locomotor activity indicating behavioral and cognitive impairment. Biochemical studies showed that D-gal significantly increases the oxidative stress and acetylcholinesterase activity (AChE) in rat brain. Histopathological study showed that D-gal disturbs the normal architecture of hippocampal and cortical cells, indicating degeneration in these brain areas. D-gal and CAE co-treatment for 42 days attenuated the behavioral, biochemical, and neuroanatomical impairments caused by the D-gal; it markedly suppresses the D-gal-induced oxidative stress and AChE activity in the brain, and maintains the normal cellular architecture in hippocampal and cortical areas. Thus, this study shows that CAE can protect the brain from the adverse effects of D-gal (e.g., memory loss and cognitive impairment) by modulating AChE activity and oxidative stress. © 2020 Informa UK Limited, trading as Taylor & Francis Group.